Transforming land rights, improving rural livelihoods, andcarving just responses to the climate crisis - Najjar, Dina; Shadrack, Naomi; Ahmed, Sara (Taylor and Francis Group, 2025)
The intersection of gender, land rights, climate change, and governance remains a focal point of contemporary discussions on justice, sustainability, and development. Women, despite their extensive contributions to agriculture, water management, and environmental conservation, continue to face systemic exclusion from control and decision-making around land tenure and climate adaptation policies and practices. Indigenous, Black, and Dalit women face further exclusion, dispossessions, and displacements in the context of commodification of land and water resources. Despite the presence of international laws that guarantee the rights of Indigenous peoples to self-determination, territories, and resources, governments, along with extractive industries such as mining, energy, oil, and housing corporations, have been seizing community-held land and forests across North America, Latin America and the Caribbean (LAC), Africa, and Asia (Smith and Allen Citation2023; United Nations (UN) Citation2022; Veit Citation2018). This systemic dispossession, driven by land grabs orchestrated by states and corporations, particularly targeting Indigenous communities, exacerbates their vulnerability by rendering them landless and destitute.